Analysis and prediction of China's future pension industry based on fitting algorithm and BP neural network. Issue 4 (June 2021) - Wu, Lijie; Cao, Yuhan; Zhang, Zixi
Abstract: In this paper, we analyze and forecast China's future pension industry. We first use the fitting algorithm to predict the number of elderly population in the future. Then BP neural network is used to predict the willingness of the elderly at all levels to stay in pension institutions, and then the market demand scale of the number of elderly service beds in China in the future is obtained. Finally, we get that in 2023, the demand for elderly care beds in China is expected to reach 16.7 million, and urban beds will dominate, accounting for 86.83% of all beds.